Structural Model of the Relationship Between Social Media Addiction in Students Based on Behavioral Brain Systems: The Mediating Role of Chronotype - Ali Mirzaei, Sajedeh; Rajabpour, Mojtaba (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to examine a structural model of social media addiction based on behavioral brain systems, with the mediating role of chronotype among university students.Methods and Materials: The research design was descriptive-correlational using structural equation modeling. The statistical population included all students of the Islamic Azad University, Semnan Branch, during the 2023–2024 academic year. From this population, 326 participants were selected through convenience sampling. The research instruments included the Behavioral Inhibition System/Behavioral Activation System (BIS/BAS) scales developed by Charles S. Carver and Teri L. White, the Morningness–Eveningness Questionnaire (MEQ) by Jim Horne and Olov Östberg, and the Social Media Addiction Questionnaire developed by Khajehahmadi et al. Data analysis was conducted using SPSS-25 and Amos software.Findings: The results indicated that social media addiction was positively associated with both the Behavioral Activation System (BAS) and the Behavioral Inhibition System (BIS), and negatively and significantly associated with morning chronotype. Structural equation modeling findings confirmed that the Behavioral Activation System had both a direct and an indirect effect—through a decrease in morningness score (i.e., a tendency toward eveningness)—on increasing social media addiction. However, the mediating role of chronotype in the relationship between the Behavioral Inhibition System and addiction was not supported.Conclusion: The findings suggest that chronotype, as a physiological substrate, facilitates the pathway through which neural sensitivities—particularly the reward system—are translated into addictive behaviors. Accordingly, therapeutic and preventive interventions in the domain of emerging addictions should, in addition to psychological factors, focus on the regulation of circadian rhythms and the modification of students’ temporal lifestyle patterns.